2012
DOI: 10.1002/asi.22722
|View full text |Cite
|
Sign up to set email alerts
|

The structure of argument patterns on a social Q&A site

Abstract: This study investigates the argument patterns in Yahoo! Answers -a major question and answer (Q&A) site. Mainly drawing on the ideas of Toulmin, argument pattern is conceptualized as a set of five major elements: claim, counter-claim, rebuttal, support and grounds. The combinations of these elements result in diverse argument patterns. Failed opening consists of an initial claim only, while non-oppositional argument pattern also includes indications of support. Oppositional argument pattern contains the elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The authors found that many content contributors posted additional information—that is, “reinforcement of content expertise”—including supplementary images and/or provided feedback to their audience, and these interactions with the audience provided the content contributors with an additional chance to promote their knowledge and expertise to the audience of the social sites. These findings are in line with Savolainen's () finding that people tend to perceive answers on social Q&A sites as more credible when the content provides further evidence and/or competing answer candidates.…”
Section: Operationalization Of Credibility On the Websupporting
confidence: 90%
“…The authors found that many content contributors posted additional information—that is, “reinforcement of content expertise”—including supplementary images and/or provided feedback to their audience, and these interactions with the audience provided the content contributors with an additional chance to promote their knowledge and expertise to the audience of the social sites. These findings are in line with Savolainen's () finding that people tend to perceive answers on social Q&A sites as more credible when the content provides further evidence and/or competing answer candidates.…”
Section: Operationalization Of Credibility On the Websupporting
confidence: 90%
“…Researchers have mainly been interested in how people seek and share UGC‐based health information (e.g., Eichhorn, ; Savolainen, ). In addition, there are studies focusing on the seeking and sharing of UGC in fields such as consumer behavior (Savolainen, ), global warming (Savolainen, ), and investing (O'Connor, ). As a whole, however, there is a paucity of studies examining the role of UGC in everyday contexts other than health.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on Toulmin´s (2003) model, Savolainen (2012) examined the ways in which argument patterns are structured in Yahoo! Answers discussion threads focusing on the issues of global warming.…”
Section: Argumentation Patterns In Qanda Discussionmentioning
confidence: 99%
“…Answers discussion about global warming (Savolainen, 2012;2013). The present study focuses on the same topic since global warming provides a fertile ground for rhetorical struggle Yahoo!…”
Section: Introductionmentioning
confidence: 99%